Wounded warrior, wounded home : hope and healing for families living with PTSD and TBI - Waddell, Marshéle Carter (Revell, 2013)
"The wife of a combat veteran and a licensed counselor help families to cope and heal in the aftermath of a service member returning home with PTSD and TBI"